Predação de ninhos da tartaruga tigre-d.água, Trachemys dorbigni (Duméril & Bibron, 1835) (Emydidae), no extremo sul do Brasil - Gonçalves, Fernanda Anziliero (2007)
Nests of the Brazilian slider turtle, Trachemys dorbigni, were monitored to evaluate predation rates and the variation in time on these rates; to identify predator species and its importance to nest destruction; and to determine the influence of nest dispersion on predation, in Southern Brazil. From 58 monitored nests, 98 % (n = 57) were destroyed by predators. Using camera traps and direct observations six species of nest predators were registered: Tupinambis merianae, Caracara plancus, Cerdocyon thous, Lycalopex gymnocercus, Conepatus chinga and Euphractus sexcinctus. Predation events occurred predominantly in the first 48 hours after oviposition. Nests constructed along all egg laying period had the same chance of being depredated. There was not prevalence of any predator. Nest density did not influence predation rate. There was no correlation between nest density and predation rates, but there was a negative correlation between time after egg laying and predation.